A facile method to control the phase behavior of hydroxypropyl cellulose. (1st January 2021) - Gosecki, Mateusz; Setälä, Harri; Virtanen, Tommi; Ryan, Anthony J.
Graphical abstract: Highlights: Hydroxypropyl cellulose methylcarbamate was synthesized in the reaction of HPC with N-methyl carbamoylimidazole. The LCST of HPC decreases linearly with the degree of substitution with methylcarbamate groups. Methylcarbamate modification of HPC has a minor effect on the aqueous solution behaviour of the macromolecules below LCST. Abstract: We report a facile chemical method to convert the hydroxyl groups of hydroxypropyl cellulose (HPC) into carbamates. It was achieved by the reaction of HPC with N-methyl carbamoylimidazole, which is a safe and easy to handle replacement for the particularly hazardous reagent methyl isocyanate. Using a series of HPC with a range of molar substitution of hydroxypropyl groups, we synthesized HPC methylcarbamates showing lower critical solution temperature (LCST) in the range between 94 and 15 °C. A linear dependence of LCST versus methylcarbamate degree of substitution is observed. The lower the initial hydroxypropyl content of HPC, the greater the effect of methylcarbamate on the LCST. Surface tension study showed that methylcarbamate modification has an insignificant effect on the hydrophilic-hydrophobic balance of the macromolecules below LCST unless the molecular substitution of hydroxypropyl groups is so low (0.8) that the native cellulose OH groups can react with N-methyl carbamoylimidazole.